Methodological considerations and functional correlates in structural MR image analysis of the brain - O'Hanlon, Erik (Trinity College (Dublin, Ireland). School of Psychology, 2008)
Structural magnetic resonance imaging is a complex and extremely powerful high resolution imaging mechanism that yields excellent soft tissue contrast. Recent times have seen the development numerous structural image analysis techniques that offer the researcher a means to perform whole brain voxelwise comparisons between various groups to capture and localize between-group differences. However, the researcher must be aware of the complexities involved in such analysis techniques and understand the implications of methodological variations. Addressing some of these concerns and applying these findings to perform inter-modal comparisons between functional MRI activation measures and structural volumetric measures to assess structure/function relations of the brain is the focus of this thesis
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin